Assessing the safety features of electronic patient medication record systems used in community pharmacies in England - Ojeleye, Oluwagbemileke; Avery, Anthony J.; Boyd, Matthew J. (Wiley, 2014)
Aims: To evaluate the ability of electronic patient medication record (ePMR) systems used in community pharmacies in England to detect and alert users about clinical hazards, errors and other safety problems. Methods: Between September 2012 and November 2012, direct on-site observational data about the performance of ePMR systems were collected from nine sites. Twenty-eight scenarios were developed by consensus agreement between a general practitioner and two community pharmacists. Each scenario was entered into the ePMR system, and the results obtained from the assessment of six unique systems in nine sites, in terms of the presence or absence of an alert, were recorded onto a prespecified form. Results: None of the systems produced the correct responses for all of the 28 scenarios tested. Only two systems provided an alert to penicillin sensitivity. No dose or frequency check was observed when processing a prescription for methotrexate. One system did not warn about nonsuitability of aspirin prescribed to a child of 14 years of age. In another system, it was not possible to record a patient's pregnancy status. None of the six systems provided any warning for diclofenac overdose, high initiation dose of morphine sulfate or significant dose increase. Only one of the systems did not produce any spurious alerts. Conclusions: The performance of the ePMR systems tested was variable and suboptimal. The findings suggest the need for minimum specifications and standards for ePMR systems to ensure consistency of performance.